Comunicação pública e as agências reguladoras brasileiras : aproximações (im) possíveis - Cidade, Daniela Firmino (2019)
Our research object are the organizations called brazilian regulatory agencies, and we have as research goals: to understand how the communication of the brazilian regulatory agencies is constituted; analyze the "place" of dialogue between regulatory agencies and citizens; evidence the contribution of brazilian regulatory agencies to public communication and the exercise of citizenship. In order to meet the proposed objectives, we used the organizational conceptions elaborated by Etzioni (1974, 1989), Srour (2012), Chanlat (2010), Max Weber (2004) and Mumby (2013). We also articulate culture concepts, using Hall (2001), Geertz (2012) and Bauman (2007), and communication, using Curvello (2009), Lima (2008) and Pinto (2008). Duarte (2012), Matos (2011, 2016), Weber (2011, 2017), Rolando (2011) and Esteves (2011) subsidize our understanding of public communication. Based on the Depth Hermeneutics, proposed by Thompson (1995), we discuss public communication using normative and factual dimensions (ESTEVES, 2011) and the strategic dimension (WEBER, 2011). We chose to deepen our analysis with the first agency created in Brazil, Agência Nacional de Energia Elétrica (ANEEL, National Electric Energy Agency). Considering Weber's proposal (2011), of public communication as an instance that shelters the concept and praxis capable of giving quality to democracies, we identify, on the part of the agencies, informative communicative practices, that do not collaborate for the development of participatory/dialogical processes and therefore do not contribute to the exercise of citizenship.